A Better Process, a Stronger UN Secretary-General: How Historic Change Was Forged and What Comes Next. Issue 2 (9th June 2017) - Terlingen, Yvonne
Abstract : When on October 13, 2016, the General Assembly appointed by acclamation António Guterres of Portugal as the United Nations' ninth secretary-general, there was a sense of excitement among the organization's 193 members. For once, so it seemed, they felt they had played an important role not only in choosing the secretary-general but also in appointing a man generally considered to be an outstanding candidate for a position memorably described as "the most impossible job on this earth." The five permanent, veto-wielding members of the Security Council (Perm Five) still exercised the greatest power in the selection process, as they always had in the past. Yet the candidate chosen appears, surprisingly, not to have been the first choice of either the United States or Russia, two of the Perm Five that until then had effectively chosen the secretary-general between them in an opaque and outdated process. It is doubtful that António Guterres would have been appointed if the General Assembly had not embarked on a novel process to select him.